Digital health interventions for adults with type 2 diabetes: Qualitative study of patient perspectives on diabetes self-management education and support - Pal, K; Dack, C; Ross, J; Michie, S; May, C; Stevenson, F; Farmer, A; Yardley, L; Barnard, M; Murray, E (Journal of Medical Internet Research, 2018)
Background The prevalence of type 2 diabetes is increasing globally and health services in many countries are struggling with the morbidity, mortality and costs associated with the complications of this long-term condition. Diabetes self-management education and behavioural support can reduce the risks of developing diabetes-related complications and improve glycaemic control. However, their uptake is low. Digital health interventions can provide sustained support and may overcome challenges with attendance at diabetes self-management sessions. They have the potential for delivery at multiple locations at convenient times, anonymity, and presentation of content in attractive and tailored formats. This study investigates the needs and wants of patients with type 2 diabetes to inform the development of digital self-management education and support. Objective To explore patient perspectives on unmet needs for self-management and support and the role of digital health interventions in adults living with type 2 diabetes. Methods Qualitative study based on data generated from four focus groups with 20 patients. Results The data generated by the focus groups illustrated the significant burden that the diagnosis of diabetes places on many patients and the negative impacts on their emotional wellbeing, work, social life and physical health. Although patients’ experiences of the health care services varied, there was agreement that even the best services were unable to meet all users’ needs to support the emotional regulation, psychological adjustment and behavioural changes needed for successful self-management. Conclusions By focusing on medical management and information provision, existing healthcare services and education programmes may not be adequately meeting all the needs of patients with type 2 diabetes. Digital health interventions have the potential to improve access to diabetes self-management education and behavioural support and extend the range of content offered by health services to fit with a wider range of patient needs. Features that could help digital health interventions meet some of the unmet needs described by participants in this study included placing an emphasis on emotional and role management, being available at all times, having up-to-date evidence based guidance for patients and providing access to peer-generated and professional advice.